Spatial changes in park visitation at the onset of the pandemic. - Kelsey Linnell; Mikaela Irene Fudolig; Aaron Schwartz; Taylor H Ricketts; Jarlath P M O'Neil-Dunne; Peter Sheridan Dodds; Christopher M Danforth (Public Library of Science (PLoS), 2022)
The COVID-19 pandemic disrupted the mobility patterns of a majority of Americans beginning in March 2020. Despite the beneficial, socially distanced activity offered by outdoor recreation, confusing and contradictory public health messaging complicated access to natural spaces. Working with a dataset comprising the locations of roughly 50 million distinct mobile devices in 2019 and 2020, we analyze weekly visitation patterns for 8,135 parks across the United States. Using Bayesian inference, we identify regions that experienced a substantial change in visitation in the first few weeks of the pandemic. We find that regions that did not exhibit a change were likely to have smaller populations, and to have voted more republican than democrat in the 2020 elections. Our study contributes to a growing body of literature using passive observations to explore who benefits from access to nature.